Different clinical and pathological profiles of sudden cardiac death victims caused by coronary artery dissection or myocardial infarction with non-obstructed coronary arteries. (3rd October 2022) - Ciliberti, G; Finocchiaro, G; Guerra, F; Papadakis, M; Sharma, S; Sheppard, M
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is a potential cause of acute coronary syndrome and sudden cardiac death (SCD). Coronary fibromuscolar dysplasia (FMD) has been correlated to SCAD occurrence.The prevalence of SCAD and FMD among SCD victims are unclear. Myocardial infarction with non-obstructed coronary arteries (MINOCA) could represent a cause of SCD. Since SCAD could clinically manifest as acute myocardial infarction, expert consensus documents have often considered SCAD as a subtype of MINOCA (1, 2), but studies which address direct comparison between these two conditions are lacking. Purpose: To assess characteristics of decedents with SCAD and/or FMD found at autopsy, and to compare their clinical and pathological profile with MINOCA SCD victims. Methods: We reviewed a database of 5325 consecutive cases of SCDs referred to our cardiac pathology center between 1994 and July 2017. Results: We identified 21 (0.4%) with SCAD and 37 (0.7%) victims with MINOCA (3), whereas FMD was found only in 2 (0.04%). SCAD decedents were females in 81%, versus 38% of MINOCA (p=0.02). No signs of coronary FMD were found among SCAD and MINOCA victims. Necrotic myocardium was identified in the totality of MINOCA and only in 8 (38%) of SCAD decedents (p<0.001). Pre-mortem cardiac symptoms were present in 100% of SCAD and 49% of MINOCA victims (p<0.001); illicit drug use was reported in none of SCAD versus 46% of MINOCA decedents (p=0.001). Conclusions: SCAD is a rare cause of SCD. Compared to MINOCA, SCAD victims are more frequently females, always experienced pre-mortem cardiac symptoms and have no habit of substances abuse. At autopsy coronary FMD is not present among SCAD victims. SCAD and MINOCA shows different clinical and pathological profile. SCAD should not be considered a subtype of MINOCA. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Cardiac Risk in the Young (CRY) and the Charles Wolfson Charitable Trust.